Learning Arabic as an L2: Study on the impact of Online Learning on Speaking Skills - Elni Desriwita; Ahmad Lahmi; Riki Saputra (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
Arabic as a foreign language for Indonesians is an important part, but in reality learning Arabic as L2 is faced with various serious problems, this is further exacerbated by the learning carried out in Covid-19. This research aims to reveal the impact of online learning on learners' Arabic language skills particularly on aspects of speaking skills. This research is carried out with a qualitative approach, data collection techniques are carried out with observations, interviews and documentation studies. Based on the results of the study, it was found that online learning greatly impacted the speaking competence Arabic language. Learning Arabic as L2 in boarding schools that are carried out online causes many learners who do not hear both arabic words and sentences spoken by teachers, the desire to repeat the teacher's speech and students are afraid because it is not clear what will be said. This reality may be due to inadequate and inaccuracy in the selection of media, but from the existing data the ability of learners to speak using Arabic does not show an increase. The recommendation of this study is that learning Arabic as L2 should maximize offline learning forms.